Active Electrode Material

Niobium mixed oxides with a Wadsley-Roth crystal structure address the limitations of graphite and LTO anodes by providing high capacity and safety in fast-charging lithium-ion batteries, suitable for high-power applications.

JP2025500407AActive Publication Date: 2025-01-09ECHION TECH LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024537883
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-02-10
Filing Date
2022-12-14
Publication Date
2025-01-09
Estimated Expiration
2042-12-14

AI Technical Summary

Technical Problem

Existing lithium-ion batteries face limitations in high-power and fast-charging applications due to graphite anodes, which suffer from lithium dendrite formation leading to safety issues, and alternative materials like lithium titanate (LTO) have low specific capacity and require complex particle engineering, reducing energy density and increasing costs.

Method used

The use of niobium mixed oxides with specific crystal structures, such as the Wadsley-Roth 4×4 octahedral block structure, which offer high redox voltage and capacity, enabling safe and efficient fast charging without the need for extensive particle-level engineering.

Benefits of technology

Niobium mixed oxides provide high capacity retention at high charging rates, enhancing battery performance for fast charge/discharge cycles while maintaining safety, thus suitable for high-power applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025500407000008
    Figure 2025500407000008
  • Figure 2025500407000009
    Figure 2025500407000009
  • Figure 2025500407000010
    Figure 2025500407000010
Patent Text Reader

Abstract

The present invention relates to an electrode comprising a niobium mixed oxide as an active electrode material. The electrode can be used in metal ion batteries, such as lithium ion batteries. The niobium mixed oxide has the formula M I x-u M y (x / (5-y)) M V z Nb 100-(x / (5-y))-z O 250-u / 2 wherein M I is a cation with an oxidation state of 1, and M y is a cation with average oxidation state y, M V is a cation with an average oxidation state of 5, with 1≦y≦4, 0.5≦x≦6, 0≦z≦10, 0≦u≦5, and x>u.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to active electrode materials, methods for producing active electrode materials, and electrodes comprising active electrode materials. Such materials are of interest, for example, as anode materials, as active electrode materials in metal-ion batteries, such as lithium-ion batteries or sodium-ion batteries. [Background technology]

[0002] Lithium-ion (Li-ion) batteries are a type of commonly used rechargeable battery, with the global market predicted to grow to $200 billion by 2030. Li-ion batteries are the technology of choice for electric vehicles, which meet multiple requirements from technical capabilities to environmental impact, providing a viable path towards a greener automotive industry.

[0003] A typical lithium-ion battery consists of multiple cells connected in series or parallel. Each cell usually consists of an anode (negative electrode) and a cathode (positive electrode), separated by a porous, electrically insulating membrane (called a separator) and immersed in a liquid (called the electrolyte) that allows the transport of lithium ions.

[0004] In most systems, the electrode consists of an active electrode material, meaning that it can chemically react with lithium ions to reversibly store and release them in a controlled manner, optionally mixed with conductive additives (such as carbon) and a polymeric binder. A slurry of these components is coated as a thin film onto a current collector (typically a thin foil of copper or aluminum) so that when dried, it forms the electrode.

[0005] In known Li-ion battery technologies, graphite anodes have safety limitations during battery charging, which is a major obstacle for high-power electronic, automotive and industrial applications. Among various promising alternatives recently proposed, lithium titanate oxide (LTO) and niobium mixed oxide are promising candidates to replace graphite as the optimal active material for high-power and fast-charging applications.

[0006] Batteries relying on graphite anodes are fundamentally limited in terms of charge rate. Under nominal conditions, lithium ions are inserted into the anode active material during charging. At higher charge rates, typical graphite voltage profiles are at high risk of overpotentially driving the potential of the anode site below 0V vs. Li / Li+, resulting in lithium ions instead depositing as lithium metal on the surface of the graphite electrode, a phenomenon known as lithium dendrite electroplating. This results in an irreversible loss of active lithium and therefore a rapid loss of cell capacity. In some cases, these dendritic deposits can grow to such a large size that they can penetrate the battery separator, leading to a short circuit of the cell. This can trigger a catastrophic failure of the cell, resulting in fire or explosion. Therefore, the fastest charging batteries with graphite anodes are limited to charge rates of 5-7C, but often significantly lower.

[0007] Lithium titanate (LTO) anodes have excellent cycle life because they are not subject to dendrite electroplating at high charge rates due to their high potential (1.6 V vs. Li / Li+) and are not subject to significant volume expansion of the active material upon lithium ion intercalation due to their 3D crystalline structure. For these two reasons, LTO cells are generally considered to be safer cells. However, LTO is a relatively poor electronic and ionic conductor, limiting its high rate capacity retention and power capability unless the material is nano-scaled to increase its specific surface area and carbon-coated to increase its electronic conductivity. This particle-level material engineering increases the porosity and specific surface area of ​​the active material, significantly reducing the packing density achievable in the electrode. This results in a lower density electrode and a higher proportion of electrochemically inactive materials (e.g., binders, carbon additives), leading to a significant reduction in gravimetric and volumetric energy density.

[0008] An important indicator of anode performance is the volumetric capacity (mAh / cm) of the electrode. 3), i.e., the amount of charge (i.e., lithium ions) that can be stored per unit volume of the anode. This amount, when combined with the cathode and appropriate cell design parameters, is a key factor in determining the overall battery energy density (Wh / L) on a volumetric basis. The volumetric capacity of an electrode is related to the electrode density (g / cm 3 ), the specific capacity of the active material (mAh / g), and the fraction of active material in the electrode. LTO anodes typically have a relatively low specific capacity (~165 mAh / g, compared to ~330 mAh / g for graphite), which accounts for the low electrode density mentioned above (typically 2.0 g / cm 3 This, combined with the small proportion of active material (less than 90%), results in a very small volumetric capacity (300 mAh / cm 3 LTO batteries / cells have a low energy density (less than 1000 kWh) and therefore a high $ cost per kWh for many applications. As a result, LTO batteries / cells are generally limited to niche applications, despite their long cycle life, fast charging capabilities, and high safety.

[0009] Niobium mixed oxides have been known in the academic literature for some time. Recently, some niobium mixed oxide structures have been of interest for use in Li-ion cells. For example, Zhu et al., J. Mater. Chem. A,2019, 7,25537 and Zhu et al., Chem. Commun., 2020,56, 7321-7324, have proposed Zn2Nb as a possible active electrode material. 34 O 87 and Cu2Nb 34 O 87These papers rely on complex particle-level engineering to purportedly achieve superior properties while trying to control, for example, particle porosity and morphology. WO2021 / 074593 and WO2021 / 074594 disclose various substituted and / or oxygen-deficient niobium mixed oxides that have been found to have superior properties for use as active electrode materials. However, there remains a need to identify additional niobium mixed oxides with superior properties for use as active electrode materials, particularly for use in Li-ion cells for high power / fast charging applications. Identifying these materials, which do not require, for example, extensive particle-level engineering and / or coating, is an important step towards low-cost battery materials for mass market adoption. Summary of the Invention

[0010] In a first aspect, the present invention relates to an electrode comprising a niobium mixed oxide as active electrode material, the niobium mixed oxide being of formula M I x-u M y (x / (5-y)) M V z Nb 100-(x / (5-y))-z O 250-u / 2 An electrode having

[0011] The niobium mixed oxide, as defined in the claims, has the formula B a M v z Nb 100-a-z O 250-a It is also possible to have

[0012] The niobium mixed oxides, as defined in the claims, are of the formula M b Nb 100-b O 250-2.5b+bc It is also possible to have

[0013] The inventors have discovered, as shown in this example, that electrodes according to the first aspect retain surprisingly high capacity even when delithiated at high rates, for example 5 C and 10 C. These are important results in demonstrating the advantages of the niobium mixed oxides of the invention for use in high power batteries designed for fast charge / discharge.

[0014] In a second aspect, the present invention provides a metal-ion battery comprising a niobium mixed oxide as an active electrode material, the niobium mixed oxide being as defined in the first aspect. Optionally, the metal-ion battery is a lithium-ion battery or a sodium-ion battery, preferably a lithium-ion battery.

[0015] In a third aspect, the present invention provides the use of a niobium mixed oxide as defined in the first aspect as an active electrode material in a metal-ion battery. Optionally, the metal-ion battery is a lithium-ion battery or a sodium-ion battery, preferably a lithium-ion battery.

[0016] In a fourth aspect, the present invention provides a method for producing an electrode comprising obtaining a niobium mixed oxide as defined in the first aspect and depositing the niobium mixed oxide on a current collector, thereby forming an electrode.

[0017] The principles of the present invention will now be described with reference to the accompanying drawings. [Brief description of the drawings]

[0018] [Figure 1] XRD patterns of selected synthetic Wadsley-Roth 4 × 4 octahedral block structures. [Diagram 2] TEM micrographs and selected area electron diffraction obtained using a Thermo Scientific (FEI) Talos F200X G2 TEM of sample 11. Left: High magnification image showing highly crystalline structure. Right: Selected area electron diffraction with (110) interplanar distance matching determined by XRD. [Diagram 3] XRD pattern of sample 18 collected using a CuKα X-ray source. [Figure 4] Voltage vs. state of charge / discharge curves for the second cycling of samples 3 and 18 in half cells using a C-rate of C / 10 from 3.0 V to 1.1 V. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] The term "niobium mixed oxide" refers to an oxide containing niobium and at least one other cation. Niobium mixed oxides have a high redox voltage vs. lithium, greater than 0.8 V, allowing for safe, long-life operation, essential for fast charging of battery cells. In addition, the niobium cation can undergo two redox reactions per atom, resulting in a higher theoretical capacity than e.g. LTO.

[0020] Niobium mixed oxides have the formula M I x-u M y (x / (5-y)) M V z Nb 100-(x / (5-y))-z O 250-u / 2 wherein M I is a cation with oxidation state 1, M y is a cation with average oxidation state y, M V is a cation with an average oxidation state of 5, 1≦y≦4, 0.5≦x≦6, 0≦z≦10, 0≦u≦5, x>u.

[0021] Niobium mixed oxides are represented by the formula B a M v z Nb 100-a-z O 250-a wherein M V is a cation with an average oxidation state of 5, 0≦z≦10, 0 <a≦8である。

[0022] Niobium mixed oxides have the formula M b Nb 100-b O 250-2.5b+bc wherein M is a cation selected from P, B, W, Mo, V, Ti, Si, and mixtures thereof; c is half the average oxidation state of M, 1.5≦c≦3, and 0.5 <b≦6である。

[0023] Niobium mixed oxides having the formula defined herein are unified because they can adopt crystal structures that are believed to contribute to their advantageous properties for use as active electrode materials. In particular, niobium mixed oxides can adopt crystal structures having a Wadsley-Roth crystal structure that includes 4×4 octahedral blocks. The Wadsley-Roth crystal structure is believed to be a crystallographic off-stoichiometry of the MO3(ReO3) crystal structure that includes crystallographic shear, and MO 3-xAs a result, these structures usually contain octahedral subunits of [MO6] in their crystal structure. In a 4×4 octahedral block structure, each block is connected only by edge-sharing octahedra. This structure was reported in 1967 to have a monoclinic unit cell (a=28.51 Å, b=3.830 Å, c=17.48 Å, β=120.80°, space group=C2 / m). This and related structures have been reported in the historical academic literature, but no electrochemical lithiation or delithiation data were provided (Andersson, Zeitschrift fur anorganische und allgemeine Chemie, Volume351, Issue 1-2, April 1967, Pages 106-112;Pekhtereva, Yu.A., & Shukaev, IL (1999), Zhurnal Neorganicheskoj Khimii, 44(2), 290-294;Cava et al 1983 J. Electrochem. Soc. 130 2345;Villafuerte-Castrejon, Journal of Solid State Chemistry, Volume 71, Issue 1, November 1987, Pages 103-108;Norin and Bertil, Acta Chemica Scandinavica, volume 25 (1971), Pages: 741-743; Reisman and Holtzberg, J. Am. Chem. Soc. 1958, 80, 24, 6503-6507). It is believed that the large block size is advantageous for fast lithium insertion and removal compared to other Wadsley-Roth structures with smaller octahedral block sizes, and may be more stable than those with larger octahedral block sizes.

[0024] The polymorph of niobium oxide N-Nb2O5 adopts the Wadsley-Roth crystal structure containing 4x4 octahedral blocks. The crystal structure of the niobium mixed oxide is therefore determined by X-ray diffraction and preferably corresponds to the crystal structure of N-Nb2O5, which is described in Andersson 1967, Zeitschrift fur anorganische und allgemeine Chemie, Volume 351, Issue 1-2, April 1967.

[0025] Compared to the experimental formula N-Nb2O5, the niobium mixed oxide according to the invention has a modified ratio of cations and anions. I x-u M y (x / (5-y)) M V z Nb 100-(x / (5-y))-z O 250-u / 2 So, some Nb is M I and M. y and the ratio of cations to anions is increased. a M v z Nb 100-a-z O 250-a In , some Nb is replaced by B, oxygen is lost from the crystal structure to maintain charge neutrality, and the ratio of cations to anions is increased, so that the crystal structure of a material with this formula may contain some tetrahedral boron cations between the 4 × 4 octahedral blocks. This modification is believed to contribute to the advantageous properties of niobium mixed oxides for use as active electrode materials. For example, changing the ratio of cations to anions is believed to stabilize the crystal structure.

[0026] The crystal structure of a material can be determined by analysis of X-ray diffraction (XRD) patterns, typically obtained from a Cu Kα source, as is widely known. For example, the XRD pattern obtained from a particular material can be compared to known XRD patterns to ascertain the crystal structure via public databases, for example the ICDD Crystallography Database. Rietveld and Pawley analyses can also be used to determine the crystal structure of a material, in particular the unit cell parameters. Thus, niobium mixed oxide can have a Wadsley-Roth crystal structure containing 4×4 octahedral blocks, as determined by X-ray diffraction.

[0027] Here, the term "corresponding" is intended to reflect that the peaks in the X-ray diffraction pattern may be shifted by 0.5 degrees or less (preferably by 0.25 degrees or less, more preferably by 0.1 degrees or less) from the corresponding peaks in the X-ray diffraction patterns of the materials listed above.

[0028] The niobium mixed oxide may adopt a monoclinic crystal structure with unit cell parameters a=25.7-31.4 Å, b=3.4-4.2 Å, c=15.8-19.3 Å, α=90°, β=112.6-137.6°, γ=90°, for example. The unit cell parameters may be determined by X-ray diffraction.

[0029] M I is a cation with oxidation state 1. M I can be selected from Li, Na, K, and mixtures thereof. Preferably, M I is selected from Li, Na, and mixtures thereof.

[0030] x is M I and the atomic weight is in the range 0.5≦x≦6. x can be an integer, for example x=1, 2, 3, 4, 5, or 6. Optionally, 2≦x≦5, for example x=2, 3, 4, or 5. Preferably, x=4.

[0031] For example, if some of the 1+ cations are lost due to volatility, usually due to their low atomic weight, the formula will contain M I may be missing. Thus, the atomic weight x may be modified by the variable 0≦u≦5, where x>u, e.g., x≧u+1. Optionally, 0≦u≦3 or 0.01≦u≦2. Alternatively, u=0.

[0032] M y is a cation with an average oxidation state of y. The term "average oxidation state" refers to the presence of multiple cations, where the oxidation state is M y It means to refer to the whole. For example, M y 1 / 3 of W 6+ So, M. y 2 / 3 of the total is Fe 3+ In this case, y is 4 (1 / 3×6(contribution from W)+2 / 3×3(contribution from Fe)). However, M y , M II , M III , M IV , and M V may consist of a single cation, in which case the oxidation state will be that of that cation.

[0033] M y may be selected from Li, Na, K, Cu, Zn, Mg, Ca, Ni, Fe, Mn, Co, Cr, V, Al, B, Ga, Sc, Y, In, La, Yb, Ce, Zr, Ti, Sn, Ge, Si, P, Ta, W, Mo, and mixtures thereof, or Li, Na, K, Cu, Zn, Mg, Ni, Fe, Mn, Co, Cr, V, Al, B, Ga, Zr, Ti, Si, P, Ta, and mixtures thereof, or Li, Na, Cu, Zn, Mg, Ni, Fe, Mn, Co, Cr, Al, B, Ga, Zr, Ti, and mixtures thereof. Optionally, M y does not contain Li.

[0034] The range of y is 1≦y≦4, but optionally 2≦y≦4. y is an integer, for example y=1, 2, 3, or 4, but preferably 2, 3, and 4. When y is an integer, it is optionally M yAll cations that form have the same oxidation state.

[0035] If y is 1, 2, 3, or 4, then M y may be selected from Li, Na, Cu, Zn, Mg, Ca, Ni, Fe, Mn, Co, Cr, Al, B, Ga, Sc, Y, In, La, Yb, Ce, Zr, Ti, Sn, Ge, and mixtures thereof.

[0036] If y is 2, 3, or 4, M y may be selected from Cu, Zn, Mg, Ca, Ni, Fe, Mn, Co, Mn, Cr, Al, B, Ga, Sc, Y, In, La, Yb, Ce, Zr, Ti, Sn, Ge, and mixtures thereof.

[0037] M y The atomic weight of M I The amount of and M y The oxidation state of the metal is related to x / (5-y).

[0038] M V is an optional cation with an average oxidation state of 5. Optionally, M V is a cation with an oxidation state of 5, and M V All cations that form have the same oxidation state, 5.

[0039] M V The atomic weight of is z, in the range 0≦z≦10. Optionally, 0≦z≦5. z can be a value greater than 0, for example, greater than 0.01. Alternatively, z=0, in which case M V does not exist.

[0040] M V may be selected from Mn, Fe, Al, Ga, Y, In, La, Yb, Cu, Zn, Mg, Ni, Co, Ca, Ce, Zr, Ti, Sn, Ge, Si, V, P, Ta, W, Mo, Cr, and mixtures thereof, or Ce, Zr, Ti, Sn, Ge, Si, V, P, Ta, W, Mo, CrV, P, Ta, and mixtures thereof, or V, P, Ta, and mixtures thereof. Optionally, MV The oxidation state of all cations that form is 5.

[0041] When y=1, the niobium mixed oxide has the formula M I x-u N I x / 4 M V z Nb 100-x / 4-z O 250-u / 2 wherein N I is a cation with oxidation state 1. I may be selected from Li, Na, K and mixtures thereof, preferably Li, Na and mixtures thereof.

[0042] When y=2, the niobium mixed oxide has the formula M I x-u M II x / 3 M V z Nb 100-x / 3-z O 250-u / 2 wherein M II is a cation with an average oxidation state of 2. II may be selected from Cu, Zn, Mg, Ni, Fe, Mn, Co, Ca, and mixtures thereof, or Cu, Zn, Mg, Ni, and mixtures thereof, or Zn, Mg, Ni, and mixtures thereof. Optionally, M II All of the cations that form have an oxidation state of 2.

[0043] When y=3, the niobium mixed oxide has the formula M I x-u M III x / 2 M V z Nb 100-x / 2-z O 250-u / 2 wherein M III is a cation with an average oxidation state of 3. M IIIcan be selected from Mn, Cr, V, Fe, Al, B, Ga, Y, In, La, Yb, Ce, and mixtures thereof, or from Mn, Cr, Fe, Al, B, Ga, Y, and mixtures thereof, or from Cr, Al, Fe, and mixtures thereof. Optionally, M III the oxidation state of all cations forming is 3.

[0044] When y = 4, the niobium mixed oxide has the formula M I x-u M IV x M V z Nb 100-x-z O 250-u / 2 wherein M IV is a cation with an average oxidation state of 4. M IV can be selected from Zr, Ti, Mn, Ce, Sn, Ge, V, Si, and mixtures thereof, or from Zr, Ti, Sn, Ge, V, and mixtures thereof, or from Ti, V, and mixtures thereof. Optionally, M IV the oxidation state of all cations forming is 4.

[0045] B a M v z Nb 100-a-z O 250-a the atomic weight of B in is a, where the range is 0 < a ≤ 8, for example 0.01 < a ≤ 8. Optionally, 1 ≤ a ≤ 5 or 1.5 ≤ a ≤ 3. a can also be an integer. Preferably, a = 2. Up to 10 at.% of the cations can be partially substituted by at least one cation selected from P, K, Fe, Ti, Zr, Sn, Ge, Zn, Mg, Al, Ga, Y, W, Mo, Cr, V, Si, Ni, Mn, Ta, Li, Na, and mixtures thereof, or from Ti, W, Mo, Cr, Zn, Al, Fe, P, and mixtures thereof.

[0046] The above-mentioned M b Nb 100-b O 250-2.5b+bcIn this case, M is a cation selected from P, B, W, Mo, V, Ti, Si, and mixtures thereof. M can be selected from P, W, B, Ti, and mixtures thereof, or P, W, and mixtures thereof. Preferably, M contains P and / or W. Up to 10 at.% of the cations can be partially substituted by at least one cation selected from K, Fe, Zr, Sn, Ge, Zn, Mg, Al, Ga, Y, Cr, Ni, Mn, Ta, Li, Na, and mixtures thereof, or Cr, Zn, Al, Fe, and mixtures thereof. b satisfies 0.5 < b ≤ 6, or 1 ≤ b ≤ 5.75, or 1.5 ≤ b ≤ 5.5. c is half of the average oxidation state of M, and 1.5 ≤ c ≤ 3, or 2 ≤ c ≤ 2.75, or 2.5.

[0047] M from a CuKα radiation source b Nb 100-b O 250-2.5b+bc In the X-ray diffraction pattern of, the full width at half maximum of the strongest peak between 18.15 and 18.65° 2θ can be greater than 0.2, and optionally greater than 0.4, greater than 0.6, and / or less than 0.9 (e.g., greater than 0.2 and less than 0.9). FIG. 3 shows the XRD pattern of a sample having this peak. The sample having this peak is considered to include the presence of some tetrahedral cations connecting between 4×4 octahedral blocks in the Wadsley-Roth crystal structure. Substances having this crystal structure have been found to have particularly high capacities.

[0048] It should be understood that the consideration of the variables in the formula (e.g., M, M I , x, u, M y , y, M v , z, a, b, c) is intended to be read in combination. For example, niobium mixed oxides can have the formula M I x-u M y (x / (5-y)) M V z Nb 100-(x / (5-y))-z O 250-u / 2 wherein, M I is Li, Na, and mixtures thereof. M y is a cation having an average oxidation state of y selected from Li, Na, Cu, Zn, Mg, Ca, Ni, Fe, Mn, Co, Cr, Al, B, Ga, Sc, Y, In, La, Yb, Ce, Zr, Ti, Sn, Ge, and mixtures thereof; M V is a cation having an average oxidation state of 5 selected from V, P, Ta, and mixtures thereof; 1≦y≦4, 2≦x≦6, 0≦z≦10, 0≦u≦3, x≧u+1.

[0049] For example, niobium mixed oxides have the formula M I x M y (x / (5-y)) Nb 100-(x / (5-y)) O 250 wherein M I is Li, Na, and mixtures thereof; M y is a cation having an oxidation state of y selected from Li, Na, Cu, Zn, Mg, Ca, Ni, Fe, Mn, Co, Cr, Al, B, Ga, Sc, Y, In, La, Yb, Ce, Zr, Ti, Sn, Ge, and mixtures thereof; M y All the cations that form have the same oxidation state, y is 1, 2, 3, or 4; x=3, 4, or 5.

[0050] M y , M I , N I , M II , M III , M IV , and M may also be selected from each of the specific elements used by themselves in the examples.

[0051] Optionally, if further cations other than Li and Nb are present, the niobium mixed oxide contains only Li. An example of such a material is Li4Cr2Nb 98 O 250 where Cr is a cation other than Li and Nb. Additionally, the niobium mixed oxide may be free of Li. It will be appreciated that the niobium mixed oxide, including the Li-free niobium mixed oxide, may reversibly intercalate Li in situ when acting as an active electrode material in a lithium ion battery.

[0052] The cations of the niobium mixed oxide may be partially replaced by further cations of different oxidation states, for example up to 20 at.%, 10 at.%, or 5 at.% of the cations may be replaced. Upon replacement by cations of different oxidation states, a charge imbalanced material is formed. The charge imbalance may be compensated for by a shortage (in the case of replacement by cations of a lower oxidation state) or an excess (in the case of replacement by cations of a higher oxidation state) of oxygen. Alternatively or in addition, the charge imbalance may be compensated for by oxidation or reduction of the cations.

[0053] The oxygen anions may be partially replaced by other electronegative anions such as F, Cl, Br, S, Se, N, and mixtures thereof. Optionally, up to 10 at.% or 5 at.% of the oxygen anions may also be partially replaced by other electronegative anions.

[0054] The niobium mixed oxide is preferably in the form of particles. The niobium mixed oxide has a diameter of D in the range of 0.1 to 100 μm, or 0.5 to 50 μm, or 1 to 20 μm. 50 These particle sizes are advantageous because they are easy to process and manufacture into electrodes. Furthermore, these particle sizes eliminate the need to use complex and / or expensive methods to produce nano-sized particles. Nano-sized particles (e.g., D of 100 nm or less) can be used. 50 Particles having a particle size of 0.1 mm or less are usually more complicated to synthesize and require additional safety considerations.

[0055] The niobium mixed oxide has a D of at least 0.05 μm, or at least 0.1 μm, or at least 0.5 μm, or at least 1 μm. 10 D 10 Maintaining the particle size in these ranges reduces the potential for parasitic reactions in Li-ion cells due to reduced surface area and allows for easier processing, requiring less binder in the electrode slurry.

[0056] Niobium mixed oxides are those with a D of 200 μm or less, 100 μm or less, 50 μm or less, or 20 μm or less. 90 D 90 By maintaining the particle size within these ranges, the proportion of the particle size distribution at larger particle sizes is minimized, making it easier to fabricate the material into a homogenous electrode.

[0057] The term "particle size" refers to the equivalent spherical diameter (esd), i.e., the diameter of a sphere having the same volume as a given particle, the volume of the particle being understood to include the volume of any intraparticle pores. n " and "D n The term "particle size" refers to the diameter below which n% by volume of the particle population is found. 50 " and "D 50 The term "particle size" refers to the volume-based median particle size below which 50% by volume of the particle population are found. It will be understood that where the material contains primary crystallites aggregated into secondary particles, the particle size refers to the diameter of the secondary particles. Particle size can be determined by laser diffraction. Particle size can be measured in accordance with ISO 13320:2009, e.g., using Mie theory.

[0058] Niobium mixed oxide is 0.1 to 100m 2 / g, or 0.2 to 50m 2 / g, or 0.5 to 20m 2The niobium mixed oxide may have a BET surface area in the range of 0.1 to 1.0 μm / g. In general, a low BET surface area is preferred to minimize the reaction of the niobium mixed oxide with the electrolyte, for example, to minimize the formation of a solid electrolyte interphase (SEI) layer during the first charge-discharge cycle of an electrode containing the material. However, if the BET surface area is too low, a large portion of the niobium mixed oxide will not be accessible to the metal ions in the surrounding electrolyte, resulting in unacceptably low charge rates and capacities.

[0059] The term "BET surface area" refers to the surface area per unit mass calculated from measurements of the physical adsorption of gas molecules on a solid surface using the Brunauer-Emmett-Teller theory. For example, the BET surface area can be determined in accordance with ISO 9277:2010.

[0060] The niobium mixed oxide may be coated with carbon, for example to improve the electrical conductivity of the surface and / or to prevent reaction with the electrolyte.

[0061] The niobium mixed oxide may have a protective coating, optionally comprising niobium oxide, aluminum oxide, zirconium oxide, organic or inorganic fluorides, organic or inorganic phosphates, titanium oxide, lithiated versions thereof, and mixtures thereof.

[0062] In the first embodiment, niobium mixed oxide forms the active electrode material of the electrode, which is preferably the anode of lithium-ion battery.However, any niobium mixed oxide defined herein can be provided as the active electrode material suitable for incorporating into electrode.For example, the niobium mixed oxide disclosed herein can be provided as a raw material for sale to, for example, electrode manufacturers, rather than as part of an electrode.

[0063] The electrode is typically in the form of an electrode composition comprising a niobium mixed oxide in electrical contact with a current collector, which is usually a metal foil such as copper or aluminum foil.

[0064] Optionally, the niobium mixed oxide forms at least 5%, 10%, or 50% by weight of the total active electrode material of the electrode. The niobium mixed oxide may form the only active electrode material of the electrode.

[0065] The electrode composition may further comprise at least one other component selected from a binder, a conductive additive, a different active electrode material (e.g., additional niobium mixed oxides as defined herein), and mixtures thereof. For example, one electrode composition comprises about 92 wt. % niobium mixed oxide, about 5 wt. % conductive additive (e.g., carbon black), and about 3 wt. % binder (e.g., poly(vinyl difluoride)), based on the total dry weight of the electrode composition.

[0066] Examples of suitable binders include polyvinylidene fluoride and its copolymers (PVDF), polytetrafluoroethylene (PTFE) and its copolymers, polyacrylonitrile (PAN), poly(methyl)methacrylate or poly(butyl)methacrylate, polyvinyl chloride (PVC), polyvinyl formal, polyetheramide, polymethacrylic acid, polyacrylamide, polyitaconic acid, polystyrene sulfonic acid, polyacrylic acid (PAA) and its alkali metal salts, modified polyacrylic acid (mPAA) and its alkali metal salts, cellulosic polymers, carboxymethylcellulose (CMC), modified carboxymethylcellulose (mCMC), sodium carboxymethylcellulose (Na-CMC), polyvinyl alcohol (PVA), alginates and their alkali metal salts, butadiene acrylonitrile rubber (NBR), hydrogenated form of NBR (HNBR), styrene butadiene rubber (SBR), and polyimides. The binder can be present in the electrode composition at 0 to 30 wt%, or 0.1 to 10 wt%, or 0.1 to 5 wt%, based on the total dry weight of the electrode composition.

[0067] The conductive additive is preferably a non-active material that is included to improve electrical conductivity between active electrode materials and between the active electrode material and the current collector. The conductive additive can be appropriately selected from graphite, carbon black, carbon fiber, vapor grown carbon fiber (VGCF), carbon nanotubes, graphene, acetylene black, ketjen black, metal fiber, metal powder, and conductive metal oxide. Preferred conductive additives include carbon black and carbon nanotubes. The conductive additive can be present in the electrode composition in an amount of 0 to 20 wt%, 0.1 to 10 wt%, or 0.1 to 5 wt%, based on the total dry weight of the electrode composition.

[0068] The active electrode material can be present in the electrode composition at 100-50 wt%, 99.8-80 wt%, or 99.8-90 wt%, based on the total dry weight of the electrode composition. When the active electrode material is present at 100 wt% of the electrode composition, it can be a solid electrode.

[0069] If a different active electrode material is present in addition to the niobium mixed oxide, it may be selected from lithium titanium oxide, titanium niobium oxide, different niobium mixed oxides, graphite, hard carbon, soft carbon, silicon, doped versions thereof, and mixtures thereof.

[0070] Niobium mixed oxides can be combined with lithium titanium oxides to form the active electrode material.

[0071] The lithium titanium oxide preferably has a spinel or ramsdellite crystal structure, for example as determined by X-ray diffraction. An example of a lithium titanium oxide having a spinel crystal structure is Li4Ti5O 12 An example of a lithium titanium oxide with the ramsdellite crystal structure is Li2Ti3O7. These materials have been shown to have excellent properties for use as active electrode materials. Thus, lithium titanium oxide is Li4Ti5O 12and / or Li2Ti3O7. Lithium titanium oxide may have a crystal structure as determined by X-ray diffraction corresponding to Li4Ti5O 12 , Li2Ti3O7, and mixtures thereof. The lithium titanium oxide may be doped with additional cations or anions. The lithium titanium oxide may be oxygen deficient. The lithium titanium oxide may include a coating, optionally the coating being selected from carbon, polymer, metal, metal oxide, metalloid, phosphate, and fluoride. The lithium titanium oxide may be synthesized by conventional ceramic techniques, such as solid state synthesis or sol-gel synthesis. Alternatively, the lithium titanium oxide may be obtained from a commercial supplier.

[0072] The lithium titanium oxide is preferably granular. The lithium titanium oxide has a diameter of D in the range of 0.1 to 50 μm, or 0.25 to 20 μm, or 0.5 to 15 μm. 50 The lithium titanium oxide may have a particle size of at least 0.01 μm, or at least 0.1 μm, or at least 0.5 μm. 10 The lithium titanium oxide may have a particle size of 100 μm or less, 50 μm or less, or 25 μm or less. 90 D 90 Maintaining the particle size in this range improves the packing of the lithium titanium oxide particles in admixture with the niobium mixed oxide particles.

[0073] Lithium titanium oxide is usually used in battery anodes with small particle sizes due to the low electronic conductivity of the material. In contrast, niobium mixed oxides as defined herein typically have a higher lithium ion diffusion coefficient than lithium titanium oxides and can be used with larger particle sizes. Advantageously, in the composition, lithium titanium oxide can have a smaller particle size than niobium mixed oxide, e.g., the D of niobium mixed oxide. 50 D of lithium titanium oxide versus particle size 50The particle size ratio of the smaller lithium titanium oxide particles is in the range of 0.01:1 to 0.9:1, or 0.1:1 to 0.7:1, in this way the smaller lithium titanium oxide particles can be accommodated in the voids between the larger niobium mixed oxide particles, increasing the packing efficiency of the composition.

[0074] Lithium titanium oxide is 0.1 to 100m 2 / g, or 1 to 50m 2 / g, or 3 to 30m 2 The nanoparticles may have a BET surface area in the range of 1 / g.

[0075] The mass ratio of lithium titanium oxide to niobium mixed oxide may be in the range of 0.5:99.5 to 99.5:0.5, preferably in the range of 2:98 to 98:2. In one embodiment, the active electrode material comprises a higher proportion of lithium titanium oxide than niobium mixed oxide, for example a mass ratio of at least 2:1, at least 5:1, or at least 8:1. Advantageously, this allows the niobium mixed oxide to be gradually introduced into existing electrodes based on lithium titanium oxide without the need to significantly change the manufacturing technology, providing an efficient way to improve the properties of existing electrodes. In another embodiment, the active electrode material comprises a higher proportion of niobium mixed oxide than lithium titanium oxide, for example a mass ratio of lithium titanium oxide to niobium mixed oxide of less than 1:2, or less than 1:5, or less than 1:8. Advantageously, this allows the cost of the active electrode material to be reduced by replacing part of the niobium mixed oxide with lithium titanium oxide.

[0076] Niobium mixed oxides can be combined with niobium oxides to form active electrode materials. Niobium oxides are Nb 12 O 29 , NbO2, NbO and Nb2O5. Preferably, the niobium oxide is Nb2O5.

[0077] Niobium oxide is, for example, a crystalline structure of an oxide composed of Nb and O, for example, Nb 12 O29 , NbO2, NbO, and Nb2O5. The niobium oxide may be oxygen deficient. The niobium oxide may include a coating, optionally selected from carbon, polymer, metal, metal oxide, metalloid, phosphate, and fluoride.

[0078] Niobium oxide is Nb as determined by X-ray diffraction. 12 O 29 , NbO2, NbO, or Nb2O5 crystal structure. For example, the niobium oxide can have an orthorhombic Nb2O5 crystal structure or a monoclinic Nb2O5 crystal structure. Preferably, the niobium oxide has a monoclinic Nb2O5 crystal structure, and most preferably has a H-Nb2O5 crystal structure. Further information regarding the crystal structure of Nb2O5 can be found in Griffith et al., J. Am. Chem. Soc.2016, 138, 28, 8888-8899. The niobium oxide can be synthesized by conventional ceramic techniques, such as solid-state synthesis or sol-gel synthesis. Alternatively, the niobium oxide can be obtained from a commercial supplier.

[0079] The niobium oxide is preferably in the form of particles. The niobium oxide has a diameter of D in the range of 0.1 to 100 μm, or 0.5 to 50 μm, or 1 to 20 μm. 50 The niobium oxide may have a particle size of at least 0.05 μm, or at least 0.5 μm, or at least 1 μm. 10 The niobium oxide may have a particle size of 100 μm or less, 50 μm or less, or 25 μm or less. 90 D 90 Maintaining the particle size in this range improves the packing of the niobium oxide particles in the mixture with the niobium mixed oxide particles.

[0080] Niobium oxide is 0.1 to 100m 2 / g, or 1 to 50m 2 / g, or 1 to 20m 2The nanoparticles may have a BET surface area in the range of 1 / g.

[0081] The mass ratio of niobium oxide to niobium mixed oxide may be in the range of 0.5:99.5 to 99.5:0.5, or in the range of 2:98 to 98:2, or preferably in the range of 15:85 to 35:55.

[0082] The present invention also provides the use of a niobium mixed oxide as defined herein in the anode of a metal-ion battery, optionally the metal-ion battery being a lithium-ion battery or a sodium-ion battery, preferably a lithium-ion battery, including liquid-based batteries, polymer-based batteries, semi-solid-based batteries and all-solid-state based batteries.

[0083] A further embodiment of the invention is an electrochemical device comprising an anode, a cathode and an electrolyte disposed between the anode and the cathode, the anode comprising an active electrode material according to the first aspect of the invention, and optionally the electrochemical device being a metal ion battery such as a lithium ion battery or a sodium ion battery. For example, the anode may be an electrode according to the first aspect of the invention. Preferably, the electrochemical device is a lithium ion battery having a reversible anode active material specific capacity of greater than 180 mAh / g at 20 mA / g, such that the battery can be charged and discharged at current densities for the anode active material of 200 mA / g or more, or 1000 mA / g or more, or 2000 mA / g or more, or 4000 mA / g or more, while retaining more than 70% of the initial cell capacity at 20 mA / g. It has been found that the use of the active electrode material of the first aspect of the invention may enable the fabrication of lithium ion batteries having this combination of properties, representing lithium ion batteries particularly suitable for use in applications where high charge and discharge current densities are desired. In particular, the examples show that the active electrode material according to the first aspect of the present invention has excellent capacity retention at high C-rates.

[0084] The electrochemical device preferably has an N / P ratio greater than 1, where N / P is defined as follows:

number

[0085] The first lithiation / delithiation capacity is measured on an equivalent half-cell. An equivalent half-cell can be understood to utilize the same electrode composition deposited at the same area loading and active fraction as the full cell. For the anode, the first constant current C / 10 lithiation (discharge, negative current) capacity (vs. Li / Li+) is measured at 25° C. For the cathode, the first constant current C / 10 delithiation (charge, positive current) capacity (vs. Li / Li+) is measured at 25° C.

[0086] It is preferred that N / P is greater than 1, for example ≧1.01. N / P may be in the range >1 to 2, or 1.01 to 1.5, or most preferably in the range 1.05 to 1.3.

[0087] The cathode is LiNi 1-x M x The active cathode material may be selected from the O2 class of nickel-based layered oxides, where M=Co, Mn, Al, such as NMC (lithium nickel manganese cobalt oxide), NCA (lithium cobalt aluminum oxide), and LCO (lithium cobalt oxide), and LNMO (lithium nickel manganese oxide) (e.g., LiNi 0.5 Mn 1.5O4). For example, the active cathode material may be lithium nickel manganese cobalt oxide. Active cathode materials are widely available from commercial suppliers. The active cathode material may be doped with additional cations and / or anions.

[0088] The choice of active electrode material may affect the range of suitable voltages, such as determining the first lithiation / delithiation capacity. For example, suitable voltage ranges may be: LNMO: 5.2-3V, with an upper cutoff of 5.2V; NCA, NMC, and LCO: 4.5-2.7V, with an upper cutoff of 4.5V; niobium mixed oxides: 3-0V, with a lower cutoff of 0V. Narrower ranges may be: LNMO: 5-3V, with an upper cutoff of 5V; NCA, NMC, and LCO: 4.3-2.7V, with an upper cutoff of 4.3V; niobium mixed oxides: 3V-1.0V, with a lower cutoff of 1.0V.

[0089] The range of suitable voltages can be determined experimentally. For example, the voltage profile correlates with the change in the energy state of the anodic and cathodic materials associated with the removal or insertion of electrons and ions. The cutoff voltage of the cell can be selected to fall before a certain inflection point in the voltage profile corresponding to the energy state of one or both electrodes rising above a critical level and causing the crystal structure to collapse into a lower energy structure at a rate significantly detrimental to the performance of the cell. The absolute voltage at which this occurs is a function of the electrode potentials of both electrodes, but can be calculated using a common reference electrode and does not need to be determined experimentally for well-established families of materials with reliable standard electrochemical behavior.

[0090] The cathode active material is preferably in particulate form, for example having a D in the range of 0.1 to 100 μm, or 0.5 to 50 μm, or 1 to 20 μm. 50 The particle size is:

[0091] The electrolyte can include any material suitable for the operation of a metal-ion battery, preferably a lithium-ion battery. For example, the electrolyte can be a non-aqueous solution (e.g., an organic electrolyte). The electrolyte can include one or more non-aqueous solvents and a salt at least partially dissolved in the solvent. For example, the solvent can include an organic solvent, such as ethylene carbonate (EC) and / or other carbonate-based solvents, or butyrate, or acetate, or a mixture thereof. The solvent can include 1M LiPF6 dissolved in an aprotic solvent mixture, such as a 1:1 weight ratio mixture of ethylene carbonate and other carbonate-based solvents or butyrate or acetate.

[0092] Salts suitable for use in the present invention include LiPF6, LiSbF6, LiBF4, LiTFSI, LiFSI, LiAlCl4, LiAsF6, LiClO4, LiGaCl4, LiC(SO2CF3)3, LiN(CF3SO2)2, Li(CF3SO3), LiB(C6H4O2)2, LiBOB (lithium bis(oxalato)borate), and LiDFOB (lithium difluoro(oxalato)borate). Suitable low viscosity solvents (e.g., organic solvents) for use in the electrolyte may include, but are not limited to, ethyl methyl carbonate (EMC), dioxolane (DOL), ethyl acetate (EA), propylene acetate (PA), butyl acetate (BA), methyl butyrate (MB), ethyl butyrate (EB), dimethyl carbonate (DMC), diethyl carbonate (DEC), 1,2-dimethoxyethane (DME), tetrahydrofuran (THF), methyl acetate (MA), diglyme (DGL), triglyme, tetraglyme, cyclic carbonates, cyclic esters, cyclic amides, propylene carbonate (PC), methyl propyl carbonate (MPC), acetonitrile, dimethyl sulfoxide (DMS), dimethylformamide, dimethylacetamide, gamma butyrolactone (GBL), and N-methylpyrrolidinone (NMP), as well as various mixtures or combinations thereof.

[0093] Niobium mixed oxide can be synthesized by conventional ceramic techniques. For example, it can be made by one or more of solid synthesis or sol-gel synthesis. Niobium mixed oxide can be further synthesized by one or more of commonly used alternative techniques, such as hydrothermal or microwave hydrothermal synthesis, solvothermal or microwave solvothermal synthesis, co-precipitation synthesis, spark or microwave plasma synthesis, combustion synthesis, electrospinning, spray pyrolysis, chemical vapor deposition, atomic layer deposition, and mechanical alloying.

[0094] The niobium mixed oxides can be obtained by a process comprising the steps of obtaining one or more precursor materials, mixing the precursor materials to form a precursor material mixture, and heat treating the precursor material mixture at a temperature range of 400°C to 1350°C or 800°C to 1250°C, thereby obtaining the niobium mixed oxides.

[0095] To obtain a niobium mixed oxide containing additional electronegative anions other than oxygen, the method may further comprise the steps of mixing the niobium mixed oxide with a precursor containing additional electronegative anions to obtain a further precursor material mixture and heat treating the further precursor material mixture, optionally under reducing conditions, in the temperature range of 300-1200° C. or 800-1100° C., thereby obtaining a niobium mixed oxide containing additional electronegative anions.

[0096] For example, to obtain a N-containing niobium mixed oxide, the method may further comprise the steps of mixing the niobium mixed oxide with a N-containing precursor (e.g., melamine or urea) to obtain a further precursor material mixture, and heat treating the further precursor material mixture under reducing conditions (e.g., under N2) in a temperature range of 300-1200°C, thereby obtaining a N-containing niobium mixed oxide.

[0097] For example, to obtain a niobium mixed oxide containing F, the method may further comprise the steps of mixing the niobium mixed oxide with a precursor containing F (e.g., polyvinylidene fluoride, or NHF) to obtain a further precursor material mixture, and heat treating the further precursor material mixture under oxidizing conditions (e.g., in air) in a temperature range of 300-1200°C, thereby obtaining a niobium mixed oxide containing F.

[0098] The method may comprise the further step of heat treating the niobium mixed oxide under reducing conditions in the temperature range of 400-1350° C. or 800-1250° C., thereby inducing oxygen vacancies in the niobium mixed oxide.

[0099] The precursor materials for making the niobium mixed oxides can include one or more metal oxides, metal hydroxides, metal salts, or ammonium salts. For example, the precursor materials can include one or more metal oxides or metal salts of different oxidation states and / or different crystal structures. Examples of suitable precursor materials include, but are not limited to, Nb2O5, Nb(OH)5, niobic acid, NbO, ammonium oxalate niobate, NH4H2PO4, (NH4)2PO4, (NH4)3PO4, P2O5, H3PO3, Ta2O5, WO3, ZrO2, TiO2, MoO3, V2O5, ZrO2, CuO, ZnO, Al2O3, K2O, KOH, CaO, GeO2, Ga2O3, SnO2, CoO, Co2O3, Fe2O3, Fe3O4, MnO, MnO2, NiO, Ni2O3, H3BO3, ZnO, Li2CO3, Na2CO3, H3BO3, NiO, Mg5(CO3)4(OH)2.5H2O, and MgO. The precursor material may not include a metal oxide or may include an ion source other than an oxide. For example, the precursor material may be a metal salt (e.g., NO3 - , SO3 - ) or other compounds (e.g., oxalates, carbonates). When replacing the oxygen anion with other electronegative anions, the precursors may include one or more organic compounds, polymers, inorganic salts, organic salts, gases, or ammonium salts, examples of which include melamine, NH4HCO3, NH3, NH4F 、These include, but are not limited to, PVDF, PTFE, NH4Cl, NH4Br, NH4I, Br2, Cl2, I2, ammonium oxychloridamide, and hexamethylenetetramine.

[0100] When it is desired to produce a niobium mixed oxide containing a cation in a particular oxidation state, a precursor containing the cation in that oxidation state can be selected. For example, Mn 2+ When preparing niobium mixed oxides containing MnO, MnO can be used as a precursor. 4+ When preparing niobium mixed oxides containing MnO2, MnO2 can be used as a precursor.

[0101] Some or all of the precursor materials may be particulate materials. If they are particulate materials, then preferably they have a diameter of less than 20 μm, for example a D of 10 nm to 20 μm. 50 Obtaining particulate material with such a particle size can help promote more intimate mixing of the precursor materials, thereby resulting in a more efficient solid-state reaction during the heat treatment step. However, it is not essential that the precursor materials have an initial particle size of less than 20 μm, since the particle size of one or more of the precursor materials can be mechanically reduced during the step of mixing the precursor materials to form the precursor material mixture.

[0102] The step of mixing the precursor materials to form the precursor material mixture and / or further precursor material mixture may be carried out by a process selected from dry or wet / planetary solvating ball milling, rolling ball milling, high energy ball milling, bead milling, pin milling, a classification step, high shear milling, air jet milling, steam jet milling, planetary mixing, powder dosing, and / or impact milling. The force used for mixing / milling may depend on the morphology of the precursor materials. For example, if some or all of the precursor materials are in a larger particle size (e.g., D > 20 μm), the precursor materials may be mixed in a larger size mixture. 50When the precursor material has a particle size of 20 μm or less, the milling force can be selected to reduce the particle size of the precursor material mixture such that the particle size of the precursor material mixture is reduced to 20 μm or less in diameter. A particle size of 20 μm or less of the precursor mixture can more efficiently promote solid-state reaction of the precursor materials of the precursor material mixture during the heat treatment step. Solid-state synthesis can also be performed on pellets formed at high pressure (greater than 10 MPa) from the precursor powder.

[0103] The step of heat treating the precursor material mixture and / or the further precursor material mixture may be carried out for a time period between 1 hour and 24 hours, more preferably between 3 hours and 18 hours. For example, the heat treating step may be carried out for 1 hour or more, 2 hours or more, 3 hours or more, 6 hours or more, or 12 hours or more. The heat treating step may be carried out for 24 hours or less, 18 hours or less, 16 hours or less, or 12 hours or less.

[0104] The step of heat treating the precursor material mixture may be carried out in a gas atmosphere, preferably air. Suitable gas atmospheres include air, N2, Ar, He, CO2, CO, O2, H2, NH3 and mixtures thereof. The gas atmosphere may be a reducing atmosphere. If it is desired to create an oxygen deficient material, preferably the step of heat treating the precursor material mixture is carried out in an inert or reducing atmosphere.

[0105] The step of heat treating the further precursor material mixture may be carried out under reducing conditions, including under an inert gas such as nitrogen, helium, argon, or under a mixture of an inert gas and hydrogen, or under vacuum. Preferably, the step of heat treating the further precursor material mixture comprises heating under an inert gas.

[0106] The further step of heat treating the niobium mixed oxide and / or the niobium mixed oxide containing additional electronegative anions, optionally under reducing conditions, can be carried out for a time period between 0.5 hours and 24 hours, more preferably between 2 hours and 18 hours. For example, the heat treatment step may be carried out for 0.5 hours or more, 1 hour or more, 3 hours or more, 6 hours or more, or 12 hours or more. The further step of heat treatment can be carried out for 24 hours or less, 18 hours or less, 16 hours or less, or 12 hours or less. Reducing conditions include under an inert gas, such as nitrogen, helium, argon, or under a mixture of inert gas and hydrogen, or under vacuum. Preferably, the heating under reducing conditions includes heating under an inert gas.

[0107] In some methods, it may be beneficial to carry out a two-step heat treatment. For example, the precursor material mixture and / or the further precursor material mixture may be heated at a first temperature for a first time, followed by heating at a second temperature for a second time. Preferably, the second temperature is higher than the first temperature. Such a two-step heat treatment may assist the solid-state reaction to form the desired crystal structure. This may be carried out consecutively or with an intermediate regrinding step.

[0108] The method may include one or more post-treatment steps after the formation of the niobium mixed oxide. In some cases, the method may include a post-treatment step of heat treating the niobium mixed oxide, sometimes referred to as "annealing". This post-treatment heat treatment step may be performed in a different gas atmosphere than the step of heat treating the precursor material mixture to form the niobium mixed oxide. The post-treatment heat treatment step may be performed in an inert gas atmosphere or a reducing gas atmosphere. Such a post-treatment heat treatment step may be performed at a temperature above 500°C, for example at about 900°C. The inclusion of a post-treatment heat treatment step may be beneficial, for example, to form deficiencies or defects in the niobium mixed oxide, such as to induce oxygen deficiencies, or to perform anion exchange, for example N exchange of O anions, in the formed niobium mixed oxide.

[0109] The method may include milling and / or classifying the niobium mixed oxide (e.g., impact milling, jet milling, steam jet milling, high energy milling, high shear milling, pin milling, air classification, wheel classification, sieving, cyclone separation, bead milling) to obtain a material having any of the particle size parameters listed above.

[0110] The present invention provides a method for producing an electrode, comprising obtaining a niobium mixed oxide as defined herein and depositing the niobium mixed oxide on a current collector to form an electrode. Obtaining the niobium mixed oxide may comprise synthesizing the niobium mixed oxide by the methods provided herein. The depositing step may comprise forming a slurry of the mixed niobium oxide and a solvent. The slurry may comprise at least one other component selected from a binder, a conductive additive, a different active electrode material, and mixtures thereof. The slurry may be deposited on the current collector and the solvent removed to form an electrode layer on the current collector. Optionally, further steps such as heat treatment to cure any binders and / or calendaring of the electrode layer may also be performed. For example, the solvent may be removed by drying, for example, at a temperature of 30-100°C. The electrode may have a density of 2-3.5 or 2.6-2.9 gcm. -3 The thickness of the electrode layer may be in the range of 5 μm to 2 mm, preferably 5 μm to 1 mm, preferably 5 μm to 500 μm, preferably 5 μm to 200 μm, preferably 5 μm to 100 μm, preferably 5 μm to 50 μm.

[0111] Alternatively, the slurry can be formed into a free-standing film or mat comprising the niobium mixed oxides, for example, by casting the slurry onto a suitable casting template, removing the solvent, and then removing the casting template. The resulting film or mat is in the form of a coherent, free-standing mass, which can then be bonded to a current collector by known methods. EXAMPLES

[0112] Niobium mixed oxides were synthesized by a solid-state route. Appropriate amounts of Nb2O5 and precursor materials were mixed and ground, for example, using a pestle and mortar or impact mill, to form a homogenous precursor mixture. The resulting mixture was heat treated at high temperatures (>800 °C) in an alumina crucible for 6–12 h with a heating rate of 5–10 ° / min. This process was repeated until the desired single phase (4 × 4 Wadsley-Roth block structure) was observed in the X-ray diffraction pattern. Specifically, stoichiometric amounts of precursor materials (Nb2O5, Li2CO3, Na2CO3, H3BO3, TiO2, Al2O3, Fe2O3, Cr2O3, NiO, and Mg5(CO3)4(OH)2.5H2O) were mixed and ground either manually in a pestle and mortar for 15 min (~5 g) or using an impact mill at 20,000 rpm for 4 min (~50 g). The resulting powders were placed in alumina crucibles and heat treated in air in a muffle furnace at T1 = 875-1150 °C, optionally at 900-1150 °C for 6-12 h. A heating rate of 5 °C / min was used for all heating steps. An additional milling and heat treatment step T2 was optionally performed to improve phase purity. Following this, a final milling step was utilized using a pestle and mortar or impact mill for deagglomeration. The compositions and synthesis parameters are summarized in Table 1. [Table 1-1] [Table 1-2]

[0113] Material characterization The phase purity of the samples was analyzed using a Rigaku Miniflex powder X-ray diffractometer in the 2θ range (10–70°) at a scan rate of 1° / min or a Bruker D8 powder diffractometer in the 2θ range, 10–50 or 10–60° (step size 0.0189°, time per step 0.42 s).

[0114] Figures 1 and 3 show the measured XRD diffraction patterns of selected samples. Figure 2 shows a TEM micrograph showing the highly crystalline structure achieved. Table 2 presents the unit cell parameters derived from the Pawley refinement based on the structure of N-Nb2O5. [Table 2]

[0115] Electrochemical characterization The charge rate of Li-ion batteries is usually expressed as "C-rate". A 1C charge rate means a charging current such that the cell is fully charged in 1 hour, while a 10C charge means that the cell is fully charged in 1 / 10 of an hour (6 minutes). The C-rate here is defined from the reversible capacity seen by the anode within the voltage limits imposed by the second delithiation cycle, i.e., 1.0 mAh cm within the voltage limits of 1.1 to 3.0 V. -2 For an anode with a capacity of 1.0 mA cm, the 1C rate is 1.0 mA cm. -2 For the typical materials described herein, this corresponds to an applied current density of about 185 mA / g active material.

[0116] Electrochemical testing was performed in half coin cells (CR2032 size) for analysis. In the half coin test, active materials are tested at the electrode against a Li metal electrode to evaluate the basic capabilities of the active material. In the following examples, the active material composition to be tested was combined with N-methylpyrrolidone (NMP), carbon black (Super P) acting as a conductive additive, and poly(vinyl difluoride) (PVDF) binder, and mixed in a laboratory scale centrifugal planetary mixer into a slurry. The non-NMP composition of the slurry was 92 wt% active material, 5 wt% conductive additive, and 3 wt% binder. The slurry was doctor blade coated onto an Al foil current collector at the desired coating weight of 50-100 g m. 2 The electrodes were then coated with 2.6–2.9 g cm−1 at 80°C and dried by heating. -3The electrodes were then calendered to a density of 10 ...

[0117] The data are averaged from 3-5 cells prepared from the same electrode coating, and the error is shown from the standard deviation. The data therefore represent a conclusive study showing the improvement achieved by the material according to the invention compared to conventional materials. These data are shown in Tables 3 and 4. The voltage vs. charge / discharge state curves for Samples 1 and 18 are shown in FIG. 4.

[0118] Also, homogeneous, smooth coatings on both Cu and Al current collector foils, free of visible defects or agglomerates, can be prepared as described above for those samples using a centrifugal planetary mixer with compositions of up to 94 wt% active material, 4 wt% conductive additive, and 2 wt% binder. These can be prepared with both PVDF (i.e., NMP-based) and CMC:SBR-based (i.e., water-based) binder systems. Coatings can be applied to 35-40% porosity and have capacities of 1.0 to 5.0 mAh cm. -2 The materials can be calendered at 80°C for PVDF and 50°C for CMC:SBR at 1000µm of load, which is important for demonstrating the viability of these materials in both high energy and high power applications with high active material content. [Table 3] [Table 4]

[0119] Consideration It has been found that the niobium mixed oxides according to the invention exhibit remarkable properties at high delithiation rates, for example at 5C and 10C. In particular, in some cases the specific capacity at low rates is largely retained at high rates, for example the capacity at 10C is 97.7% or more of the capacity at 0.5C, resulting in very high capacity retention. These are important results in demonstrating the advantages of the niobium mixed oxides according to the invention for use in high power batteries designed for high rate charge / discharge.

Claims

1. An electrode comprising a niobium mixed oxide as active electrode material, said niobium mixed oxide being represented by the formula M I x-u M y (x/(5-y)) M V z Nb 100-(x/(5-y))-z O 250-u/2 wherein M I is a cation with oxidation state 1, M y is a cation with average oxidation state y, M V is a cation with an average oxidation state of 5, 1≦y≦4, 0.5≦x≦6, 0≦z≦10, 0≦u≦5, The electrode, wherein x>u.

2. (i) M y is selected from Li, Na, K, Cu, Zn, Mg, Ca, Ni, Fe, Mn, Co, Cr, V, Al, B, Ga, Sc, Y, In, La, Yb, Ce, Zr, Ti, Sn, Ge, Si, P, Ta, W, Mo, and mixtures thereof; or (ii) M y is selected from Li, Na, K, Cu, Zn, Mg, Ni, Fe, Mn, Co, Cr, V, Al, B, Ga, Zr, Ti, Si, P, Ta, and mixtures thereof; or (iii) M y 2. The electrode of claim 1, wherein is selected from Li, Na, Cu, Zn, Mg, Ni, Fe, Mn, Co, Cr, Al, B, Ga, Zr, Ti, and mixtures thereof.

3. (i) y is 1, 2, 3, or 4; or (ii) y is 2≦y≦4; or (iii) An electrode according to any preceding claim, wherein y is 2, 3, or 4.

4. M y 4. An electrode as claimed in any preceding claim, wherein all cations forming

5. (i) M I is selected from Li, Na, K, and mixtures thereof; or (ii) M I 4. An electrode according to any preceding claim, wherein is selected from Li, Na, and mixtures thereof.

6. The niobium mixed oxide has the formula M I x-u N I x/4 M V z Nb 100-x/4-z O 250-u/2 wherein N I The electrode according to any one of claims 1 to 5, wherein is a cation having an oxidation state of 1.

7. (i) N I is selected from Li, Na, K, and mixtures thereof; or (ii) N I The electrode of claim 6 , wherein is selected from Li, Na, and mixtures thereof.

8. The niobium mixed oxide has the formula M I x-u M II x/3 M V z Nb 100-x/3-z O 250-u/2 wherein M II An electrode according to any one of claims 1 to 5, wherein is a cation having an average oxidation state of 2.

9. M II 9. The electrode of claim 8, wherein all cations forming

10. (i) M II is selected from Cu, Zn, Mg, Ni, Fe, Mn, Co, Ca, and mixtures thereof; or (ii) M II is selected from Cu, Zn, Mg, Ni, and mixtures thereof; or (iii) M II 10. The electrode of claim 8 or 9, wherein is selected from Zn, Mg, Ni, and mixtures thereof.

11. The niobium mixed oxide has the formula M I x-u M III x/2 M V z Nb 100-x/2-z O 250-u/2 wherein M III An electrode according to any one of claims 1 to 5, wherein is a cation having an average oxidation state of 3.

12. M III 12. The electrode of claim 11, wherein all cations forming

13. (i) M III is selected from Mn, Cr, V, Fe, Al, B, Ga, Y, In, La, Yb, Ce, and mixtures thereof; or (ii) M III is selected from Mn, Cr, Fe, Al, B, Ga, Y, and mixtures thereof; or (iii) M III 13. The electrode according to claim 11 or 12, wherein is selected from Cr, Al, Fe, and mixtures thereof.

14. The niobium mixed oxide has the formula M I x-u M IV x M V z Nb 100-x-z O 250-u/2 wherein M IV An electrode according to any one of claims 1 to 5, wherein is a cation having an average oxidation state of 4.

15. M IV 15. The electrode of claim 14, wherein all cations forming

16. (i) M IV is selected from Zr, Ti, Mn, Ce, Sn, Ge, V, Si, and mixtures thereof; or (ii) M IV is selected from Zr, Ti, Sn, Ge, V, and mixtures thereof; or (iii) M IV 16. The electrode of claim 14 or 15, wherein is Ti, V, and mixtures thereof.

17. (i) x is 1, 2, 3, 4, 5, or 6; or (ii) x is 2≦x≦5; or (iii) an electrode according to any preceding claim, wherein x=4.

18. (i) 0≦u≦3, or (ii) 0.01≦u≦2, or 2. An electrode according to any preceding claim, wherein (ii) u=0.

19. 10. An electrode according to any preceding claim, wherein x≧u+1.

20. 10. An electrode according to any preceding claim, wherein the niobium mixed oxide comprises only Li when further cations other than Li and Nb are present.

21. M y 13. An electrode according to any preceding claim, wherein said niobium mixed oxide is Li-free or wherein said niobium mixed oxide is Li-free.

22. Electrode comprising a niobium mixed oxide as active electrode material, said niobium mixed oxide having the formula B a M v z Nb 100-a-z O 250-a wherein M V is a cation with an average oxidation state of 5, 0≦z≦10, The electrode, wherein 0<a≦8.

23. (i) 1≦a≦5, or (ii) 1.5≦a≦3, 23. The electrode of claim 22, wherein (iii) a=2.

24. (i) M V is selected from Mn, Fe, Al, Ga, Y, In, La, Yb, Cu, Zn, Mg, Ni, Co, Ca, Ce, Zr, Ti, Sn, Ge, Si, V, P, Ta, W, Mo, Cr and mixtures thereof; or (ii) M V is selected from Ce, Zr, Ti, Sn, Ge, Si, V, P, Ta, W, Mo, Cr and mixtures thereof; or (iii) M V 4. An electrode according to any preceding claim, wherein is selected from V, P, Ta, and mixtures thereof.

25. M V 4. An electrode according to any preceding claim, wherein the oxidation state of all cations forming

26. (i) 0≦z≦5, and / or (ii) z>0, or (iii) An electrode according to any preceding claim, wherein z=0.

27. An electrode comprising a niobium mixed oxide as an active electrode material, said niobium mixed oxide having the formula M b Nb 100-b O 250-2.5b+bc wherein M is a cation selected from P, B, W, Mo, V, Ti, Si, and mixtures thereof; c is half the average oxidation state of M; 1.5≦c≦3, and The electrode, wherein 0.5<b≦6.

28. 28. The electrode of claim 27, wherein the full width at half maximum of the most intense peak between 18.15 and 18.65 degrees 2θ is greater than 0.2 in an X-ray diffraction pattern of the material using a CuKα source, and optionally the full width at half maximum is greater than 0.4, greater than 0.6, and / or less than 0.

9.

29. 29. An electrode according to claim 27 or 28, wherein M is selected from P, W, Ti, B and mixtures thereof, or P, W and mixtures thereof.

30. 10. The electrode of any preceding claim, wherein the cations are partially replaced by cations of a different oxidation state, optionally up to 20 at. % of the cations are replaced by cations of a different oxidation state.

31. 10. The electrode of any preceding claim, wherein the oxygen anions are partially replaced by alternative electronegative anions such as F, Cl, Br, S, Se, N, and mixtures thereof, and optionally up to 10 at. % of the oxygen anions are partially replaced by alternative electronegative anions.

32. The niobium mixed oxide has a D in the range of 0.1 to 100 μm, or 0.5 to 50 μm, or 1 to 20 μm. 50 13. An electrode according to any preceding claim, having a particle size of

33. The niobium mixed oxide has a viscosity of 0.1 to 100 m 2 / g, or 0.2 to 50 m 2 / g, or 0.5 to 20 m 2 13. The electrode of any preceding claim, having a BET surface area in the range of 0.1 wt. / g.

34. 10. An electrode according to any preceding claim, wherein the niobium mixed oxide is coated with carbon.

35. 13. The electrode of any preceding claim, wherein the niobium mixed oxide has a protective coating, optionally the protective coating comprising niobium oxide, aluminum oxide, zirconium oxide, organic and inorganic fluorides, organic and inorganic phosphates, titanium oxide, lithiated versions thereof, and mixtures thereof.

36. 10. An electrode according to any preceding claim, wherein the niobium mixed oxide has a Wadsley-Roth block structure comprising 4x4 octahedral blocks.

37. 10. An electrode according to any preceding claim, wherein the niobium mixed oxide has a monoclinic crystal structure, and optionally the niobium mixed oxide has unit cell parameters a=25.7-31.4 Å, b=3.4-4.2 Å, c=15.8-19.3 Å, α=90°, β=112.6-137.6°, γ=90°.

38. The crystal structure of the niobium mixed oxide is N-Nb 2 O 5 13. An electrode according to any preceding claim, which corresponds to a crystal structure of

39. 10. An electrode according to any preceding claim, wherein the niobium mixed oxide forms at least 5%, 10% or 50% by weight of the total active electrode material of the electrode, or the niobium mixed oxide is the only active electrode material of the electrode.

40. 13. The electrode of any preceding claim, further comprising at least one other component selected from a binder, a conductive additive, a different active electrode material, and mixtures thereof.

41. 41. The electrode of claim 40, wherein the different active electrode materials are selected from lithium titanium oxide, titanium niobium oxide, different niobium mixed oxides, graphite, hard carbon, soft carbon, silicon, doped and / or carbon coated versions thereof, and mixtures thereof.

42. 42. A metal-ion battery comprising an electrode according to any one of the preceding claims, optionally wherein the metal-ion battery is a lithium-ion battery and said electrode forms the anode.

43. 43. The metal-ion battery of claim 42, wherein the lithium-ion battery has a reversible anode active material specific capacity of greater than 180 mAh / g at 20 mA / g, wherein the battery can be charged and discharged at current densities for the anode active material of 200 mA / g or greater, or 1000 mA / g or greater, or 2000 mA / g or greater, or 4000 mA / g or greater, while retaining more than 70% of the initial cell capacity at 20 mA / g.

44. Electrochemical device comprising an anode, a cathode and an electrolyte disposed between the anode and the cathode, the anode comprising as an active anode material a niobium mixed oxide as defined in any one of claims 1 to 38, the device having an N / P ratio > 1, the N / P ratio being [0010] During the ceremony, Area loading (mgcm -2 ) is the drying load of the electrode composition without considering the current collector, Active Fraction (wt%) is the fraction of the dry electrode composition that is the active material; First Lithiation / Delithiation Capacity (mAhg -1 ) is defined as the specific capacity at C / 10 at 25° C. for the first lithiation cycle of the anode or the first delithiation cycle of the cathode measured in an equivalent half-cell with a Li metal counter electrode.

45. 39. Use of a niobium mixed oxide as claimed in any one of claims 1 to 38 as an active electrode material in a metal ion battery, optionally in the anode of a lithium ion battery.

46. A method for manufacturing an electrode, comprising the steps of: Obtaining a niobium mixed oxide as defined in any one of claims 1 to 38, and depositing the niobium mixed oxide onto a current collector to form the electrode.

Citation Information

Patent Citations

  • Micron spherical titanium niobate, and preparation method and application thereof

    CN110776008A

  • Modified one-dimensional TiNb24O62 as well as preparation method and application thereof

    CN110776009A

  • Negative electrode material for nonaqueous electrolyte secondary battery, negative electrode for nonaqueous electrolyte secondary battery, and nonaqueous electrolyte secondary battery using it

    JP2010287496A

  • Production method of battery active material, battery active material, nonaqueous electrolyte battery and battery pack

    JP2015111550A

  • Active electrode material

    WO2021074592A1